2015
DOI: 10.1159/000380759
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Chromoblastomycosis Caused by Fonsecaea pedrosoi

Abstract: Purpose: To report 2 unusual cases of fungal keratitis due to Fonsecaea pedrosoi. Methods: Two patients were diagnosed with Fonsecaea pedrosoi keratitis. Their files were reviewed for predisposing factors, clinical characteristics, microbiological study, treatment, and outcome. Results: Two consecutive patients presented with brownish pigmented corneal ulcers in their eyes after sustaining eye trauma from vegetative matter. In both cases, corneal scrapings were collected for microscopic examination and culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
1
3
0
9
Order By: Relevance
“…Majority gave history of trauma in the adjoining area of body. Likewise similar socioeconomic conditions and history have been cited by the study-group of Kerala [13] and Thailand [12]. But cases reported by De et al, and that of Park SG, Korea had no such history of trauma [10,11].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Majority gave history of trauma in the adjoining area of body. Likewise similar socioeconomic conditions and history have been cited by the study-group of Kerala [13] and Thailand [12]. But cases reported by De et al, and that of Park SG, Korea had no such history of trauma [10,11].…”
Section: Resultssupporting
confidence: 59%
“…Both the reports were silent about isolation of causative fungus. However, chromoblastomycotic keratitis has been reported from Thailand from two patients and both the cases were culture positive to yield Fonsacaea pedrosoi [12].…”
Section: Resultsmentioning
confidence: 93%
“… 13 , 14 What is more, invasive hyphal growth without transformation into muriform cells was observed in some special cases of corneal infection caused by F. pedrosoi . 15 17 These phenomena cohere with the term “sclerotic cells,” which was derived from “sclerotia,” and explained the parasitic form of chromoblastomycosis agents as compacted masses of latent hyphae. 3 …”
Section: Introductionmentioning
confidence: 55%
“…Although the presentation of F. pedrosoi as hyphal form in tissue can be observed in some immune-privileged organs or immunosuppressed patients, 15 17 , 31 , 32 it still leaves much to be determined whether there exists a linkage between the parasitic form of chromoblastomycosis agents and host immune status till now. Interestingly, some studies suggested that the reexposure of C57BL/6 mice to hyphae/conidida of F. pedrosoi developed lesions with muriform cells and caused a delayed resolution of the infection with relatively lower degree of neutrophilic process in comparison to mice that were not reexposed.…”
Section: Discussionmentioning
confidence: 99%
“…O local frequentemente acometido é a extremidade dos membros inferiores, seguido de membros superiores, região glútea, tronco e face. Entretanto, a doença já foi igualmente identificada em outras partes do corpo como na axila e na córnea [36,37]. Uma vez instalado no tecido, o fungo adere-se às células epiteliais e diferencia-se em estruturas parasitárias características, denominadas células muriformes e , f , as quais resistem à destruição pelas células efetoras do hospedeiro (Figura 1, B), permitindo assim o estabelecimento crônico da doença [16,38].…”
Section: íNdice De Figurasunclassified